2001
DOI: 10.1007/s127-001-8199-7
|View full text |Cite
|
Sign up to set email alerts
|

Australian general practice and the meeting of needs for mental health care

Abstract: Many people with mental health problems attend primary medical care practitioners without presenting these problems to their physicians. When they do present, perceived needs for medication are rated as well met, but there is substantial unmet perceived need for interventions in social and occupational domains. Perceived needs for counselling are less well met where the GP is the sole provider. To close these identified gaps calls for improvements in primary care physicians' skills and effective collaborative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 34 publications
4
48
0
Order By: Relevance
“…22 Several studies have also shown that people perceiving UNCs have symptoms that are more severe than people without perceived needs for care, 20 as well as higher distress. Consistent with previous studies conducted in the general population and among users of primary care services, 1,10,[12][13][14][15]19 needs related to psychotherapy are more likely to be perceived as unmet, and needs for medication as met. This is consistent with a high psychotropic consumption in Quebec, 1 where their access is easy (that is, cost and prescription).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…22 Several studies have also shown that people perceiving UNCs have symptoms that are more severe than people without perceived needs for care, 20 as well as higher distress. Consistent with previous studies conducted in the general population and among users of primary care services, 1,10,[12][13][14][15]19 needs related to psychotherapy are more likely to be perceived as unmet, and needs for medication as met. This is consistent with a high psychotropic consumption in Quebec, 1 where their access is easy (that is, cost and prescription).…”
Section: Discussionsupporting
confidence: 84%
“…For instance, over 80% of patients with common mental disorders report that their needs for medication are fully met, while only 5% report that such needs go completely unmet. 12,13 In contrast, while psychotherapy is reported to be the most frequent perceived need regarding mental health care, 14 such needs are fully met in only one-half of patients 10,12,14 and completely unmet in 13% to 26% of patients. 12,13 Other perceived needs, such as those related to health information and psychosocial interventions (for example, related to housing or employment), are also less frequently fully met.…”
mentioning
confidence: 99%
“…Perceived need for mental health care in the past six months was measured with the perceived need for care questionnaire (PNCQ) [30,31]. The PNCQ was developed to measure need for mental health care, as well as the extent to which needs are met, from the perspective of the patient.…”
Section: Measurements J Perceived Needmentioning
confidence: 99%
“…For example, Bäärnhielm and Ekblad conducted interviews with Turkish women, during which difficulties to understand the meaning of unfamiliar words, concepts, investigations and treatments came up as a very important theme [5]. Such difficulties may result in difficulties in determining personal risk, and consequently a lack of perceived need for care [31,42,44]. Additionally, cultural factors are known to affect the interpretation of symptoms [23].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Both in Canada and in other jurisdictions, family physicians are found to be the major provider visited for mental health reasons. They play a key role in the management of mental health problems 6,10,[14][15][16][17][18] and efforts and initiatives to deliver quality mental health care have shifted toward the integration of primary care and specialized mental health services. [19][20][21][22][23] The role of the family physician in mental health care relating to other providers is often unclear.…”
mentioning
confidence: 99%